Predictive factors to determine post-operative mortality in patients with peripheral arterial disease - Rungrujee Kaweewan (2018)
© 2017, Medical Association of Thailand. All rights reserved. Objective: Major vascular surgery of peripheral arterial disease (PAD) is a high post-operative mortality procedure. There are few studies in predictive factors for post-operative mortality in Asian populations. Assessing the predictive factors preoperatively can prolong survival in this population. Material and Method: The prospective study included patients with PAD who had major vascular surgery between December 2002 and December 2005 at the Maharaj Nakorn Chiang Mai Hospital. Survival status and predictive factors of mortality were analyzed. Results: One hundred one patients were included in the present study. Fifty-three patients died (62.3%) with 4.19 years of median survival time; 5-year survival was 47.28%. The predictive factors effecting mortality were hyponatremia (hazard ratio (HR) 17.69, 95% confidence interval (CI) 2.02 to 154.91), respiratory distress sign (shortness of breath at rest) (HR 12.36, 95% CI 2.12 to 71.75), atrial fibrillation (HR 3.18, 95% CI 1.39 to 7.29), abnormal plasma potassium (HR 2.80, 95% CI 1.28 to 6.15), and preoperative hypertension (HR 0.54, 95% CI 0.30 to 0.98). Conclusion: Serum hyponatremia, shortness of breath, atrial fibrillation, abnormal plasma potassium level, and hypertension were the predictive factors for high mortality in patients with PAD.